QUALITY MANAGEMENT SYSTEM OF THE UNIVERSITY AND ITS SOFTWARE AND INFORMATION SUPPORT - Kuz , M.V.; Bezghachniuk , Ya.V.; Zapukhlyak , R.I. (The actual problems of regional economy development, 2025)
The paper is aimed as researching the quality management system of the university in terms of the requirements of the international standard ISO 9001. This standard has been used by enterprises and organizations around the world for almost half a century. It is the basis for the development of quality management system models, particularly in universities. On the other side, Ukrainian legislation in the field of education regulates its own requirements for the systems of internal quality assurance. The aim of the research is quality model improvement for higher education institutions (universities). During research mathematical modeling methods and methods of system approach have been used for the clasification of local regulatory documents of the universities. During the research process, the task of systematizing the quality management system documentation was set and task of building information model for regulatory base, as well as task of forming processing approach for quality system functioning and task of building structural-logical model of the processes. The paper is devoted to development of the quality management system model on the basis of PDCA cycle. This model has input parameters formed based on requirements, needs and expectations of the stakeholders; quality system functioning module, in center of which there is an element of leadership, and cycle PDCA links such elements as planning, quality management system maintanance, educational process implementation, evaluation of performance and improvement; output parameters about satisfaction level of the students, graduates, employers and about results of university activity, in particular the knowledge level of the students and university ratings. On the basis of proposed model structural model has been developed that establishes logical relations between quality management system processes. A scientific novelty of the results obtained: university quality management system model has been developed and structural-logical model of the processes based on PDCA cycle was developed as well, that give an opportunity to implement process approach of internal university quality assurance system functioning. The practical significance of the research results lies in the formation of the regulatory framework structure of the university’s quality management system and software-information system implemented as an Electronic fund of local regulatory documents of the Vasyl Stefanyk Precarpathian National University.